NEW DOSAGE FORMS FOR THE DELAYED RELEASE OF MESALAZINE TO THE COLON - SIAMIDI, ANGELIKI; VLACHOU, MARILENA; EFENTAKIS, MANUEL (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of the present work was to develop new solid pharmaceutical delivery systems of mesalazine (5-aminosalicylic acid, 5-ASA) for its colon targeted release. Methods: Four different types of tablets of the same consistency (matrix and three-layered, with 5-ASA and dextran or pectin as excipients) were placed in a hard gelatin capsule. The 5-ASA release behavior from these formulations was compared to the release of the commercially available Asalazin® in three pH aqueous media in the presence of enzymes. Results: The produced tablet formulations conformed to the Pharmacopoeia standards. The results showed delayed-release (<10%) during the first two hours, in acidic media (pH 1.5), and modified-release thereafter (pH 6 and 7.4). When dextran was used, the drug release showed more extended-release characteristics, in comparison to pectin formulations, due to the formation of a thicker hydrogel. Conclusion: The new dosage forms could serve as a per os administration alternative dosage form for the delayed release of mesalazine to the colon